Le più antiche fondazioni di canoniche regolari a Pisa tra XI e XII secolo: vicende storiche e rappresentazione documentaria - Mastruzzo, Antonino; Rossi, Maria Cristina (Scrineum, 2016)
Our information on the foundation of Pisa’s oldest canons regular rectories, Santa Maria a Fine and San Pietro in Vincoli, comes from a series of diplomatically- anomalous documents. This essay discusses various hypotheses regarding their possible falsification, adjustment and copying. Definitively, however, it seems more plausible that said documents were drawn up at a later time than that expressly declared on the founding documents and that they should be read with an aim to retrospectively reconstruct the town’s ecclesiastic history materialised via these documents.